INTERACTION OF MANTLE-DERIVED MELTS WITH CRUST ON ITS UPWELLING TO THE SURFACE: REASON AND CONSEQUENCE - Alexei V. Ivanov (Геодинамика и тектонофизика)
The work considers the mechanism of upwelling of the basaltic melt to the surface and the reason of its stoppage in the crust. The process of stoppage, probably, is controlled by ratio between density of the basaltic melt and density of the crust. If density of the basaltic melt is lower it goes up to the surface without significant stoppage, if the opposite it stays in the crust. Because the melt density decreases with increase of its alkalinity and/ or fluid content, it explains why highly alkaline melts are characterized by low degree of crustal contamination compared to normal alkaline dry melts.